2021
DOI: 10.4314/tjpr.v18i9.7
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of electro-acupuncture in spinal cord injury rats via up-regulation of DUSP14

Abstract: Purpose: To study the effect and mechanism of action of electro-acupuncture (EA) on nerve regeneration by analyzing the behavior, inflammation and cell death in spinal cord injury (SCI) rat model. Methods: SCI model was established according to Allen’s falling strike method. Electroacupuncture was performed on Jiaji (EX-B2)/Mingmen (GV4) acupoint with a 1 mA current intermittent wave at a frequency of 2Hz for 20 min daily. Interleukin (IL-6) and tumor necrosis factor-α (TNF-α) levels were measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…DNA gel electrophoresis and TUNEL assays have been performed on SCI tissue since 1999 and are still being performed to date. With such techniques, it has been repeatedly found that DNA fragmentation occurs in the spinal cord following injury at 1 to 7 dpi [ 17 , 23 , 26 , 48 , 56 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. Though one cannot distinguish in these experiments between strand breaks in viable cells that can be resolved by DNA repair and DNA fragmentation as a consequence of apoptosis, the data add to the evidence of strand breaks occurring post-SCI.…”
Section: Oxidative Dna Damage Is Understudied After Scimentioning
confidence: 99%
“…DNA gel electrophoresis and TUNEL assays have been performed on SCI tissue since 1999 and are still being performed to date. With such techniques, it has been repeatedly found that DNA fragmentation occurs in the spinal cord following injury at 1 to 7 dpi [ 17 , 23 , 26 , 48 , 56 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. Though one cannot distinguish in these experiments between strand breaks in viable cells that can be resolved by DNA repair and DNA fragmentation as a consequence of apoptosis, the data add to the evidence of strand breaks occurring post-SCI.…”
Section: Oxidative Dna Damage Is Understudied After Scimentioning
confidence: 99%